PENGARUH KOMPENSASI, BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PERUSAHAAN DAERAH AIR MINUM (PDAM) KABUPATEN BANTUL DAERAH ISTIMEWA YOGYAKARTA - Yuyun Afifah (JURNAL EKOBIS DEWANTARA, 2018)
The purpose of this study is to determine the effect (1) Compensation on job satisfaction, (2) Organizational Culture on job satisfaction, (3) Work environment on job satisfaction (4) together Compensation, Organizational Culture, Work Environment, Job Satisfaction employees of PT PDAM Kab. Bantul. Based on the relationship between variables on the object under study, this study is causal or called causal relations. the population is the whole of the research subject is Employee PT PDAM Bantul which amounted to 220 employees.165 employees are outside or in the field and employees who are or work in the office is as many as 55 people, because researchers only need employees who are or work in the office only then 55 employees who work in the office as a sample. Methods of collecting data in the form of questionnaires. While Tekhik data analysis using multiple regression analysis. Supported by hypothesis (T) test and F test. And classical assumption test consist of Normality Test, Multicolinearity Test, and Heterocedasticity Test. The result of data analysis with significance 0,05 show that Competation have positive significant effect to job satisfaction, organizational culture have positive significant effect to job satisfaction, work environment have positive significant effect on job satisfaction. There is simultaneous influence of variable of compensation, culture and work environment to prove there is satisfaction work a significant positive effect.